Optimizing Campus Promotion Routes Through the Application of Dijkstra’s Algorithm - Siagian, Edward Robinson; Rajagukguk, Denni M Rajagukguk; Panjaitan, Muhammad Iqbal (Pascal: Journal of Computer Science and Informatics, 2025)
This study aims to optimize campus promotion routes using Dijkstra's algorithm to increase efficiency in time and cost. By applying this method, the shortest and fastest paths to target promotion locations can be optimally determined. Data were obtained through geographical mapping of schools and road accessibility. The implementation of Dijkstra’s algorithm was analyzed in terms of effectiveness and efficiency compared to conventional methods. This study is expected to contribute to enhancing the effectiveness of campus promotion strategies through route optimization.